Influence of the height of multilure traps in the collection of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) - Ribeiro, José Gabriel Gonçalves; Soares, Nyeppson de Sousa; Mesquita Filho, Walter; Araujo, Mayara Ribeiro de; Zucchi, Roberto Antonio; Savaris, Marcoandre (EntomoBrasilis, 2021)
The Mediterranean fruit fly Ceratitis capitata (Wiedemann) is a polyphagous pest adapted to tropical and subtropical climates, which are responsible for the highest share of fruit production. Fruit fly surveys are frequently done by installing traps at heights easily reached by the collector, between 1.5 and 2.5 meters. This study aims to inform fruit fly monitoring strategies by assessing two trap heights (around 2 m and 10 m) in four environments (agricultural and forest) at the “Luiz de Queiroz” Campus, Piracicaba, São Paulo state, Brazil. Each collection environment was considered a block, and eight multilure traps were installed at each of the two heights on four plants per block. A generalized linear model was used for non-normal data with negative binomial distribution to compare the abundance of C. capitata between trap heights and areas. The higher traps, positioned at around 10 m, collected significantly more specimens of C. capitata than those at approximately 2 m in height. The Mediterranean fruit fly was more frequent in the cultivated environments and areas with human activity than in natural areas.